Evaluation of Recombinant Multi-Epitope Outer Membrane Protein-Based Klebsiella pneumoniae Subunit Vaccine in Mouse Model - Babu, Litty; Uppalapati, Siva R.; Sripathy, Murali H.; Reddy, Prakash N. (Frontiers in Microbiology, 2017)
Safety and protective efficacy of recombinant multi-epitope subunit vaccine (r-AK36) was evaluated in a mouse model. Recombinant AK36 protein comprised of immunodominant antigens from outer membrane proteins (Omp’s) of Klebsiella pneumoniae namely OmpA and OmpK36. r-AK36 was highly immunogenic and the hyperimmune sera reacted strongly with native OmpA and OmpK36 proteins from different K. pneumoniae strains. Hyperimmune sera showed cross-reactivity with Omp’s of other Gram-negative organisms. Humoral responses showed a Th2-type polarized immune response with IgG1 being the predominant antibody isotype. Anti-r-AK36 antibodies showed antimicrobial effect during in vitro testing with MIC values in the range of 25–50 μg/ml on different K. pneumoniae strains. The recombinant antigen elicited three fold higher proliferation of splenocytes from immunized mice compared to those with sham-immunized mice. Anti-r-AK36 antibodies also exhibited in vitro biofilm inhibition property. Subunit vaccine r-AK36 immunization promoted induction of protective cytokines IL-2 and IFN-γ in immunized mice. When r-AK36-immunized mice were challenged with 3 × LD100 dose, ∼80% of mice survived beyond the observation period. Passive antibody administration to naive mice protected them (67%) against the lethal challenge. Since the targeted OMPs are conserved among all K. pneumoniae serovars and due to the strong nature of immune responses, r-AK36 subunit vaccine could be a cost effective candidate against klebsiellosis.